Dust Acoustic Shock Waves in Strongly Coupled Dusty Plasmas with Superthermal Electrons and Ions - Hamid Reza Pakzad (Iranian Journal of Astronomy and Astrophysics)
We use reductive perturbation method and derive the Kordeweg-de Vries-Burgers (KdV-Burgers) equation in coupled dusty plasmas containing ions and electrons obeying superthermal distribution. We discuss the effect of the plasma parameters on the shock wave structure. It is simply shown how soliton profile is converted into shock structure when the coupling force increases. In fact as long as the dispersive term and the dissipative term as well as the nonlinear term are balanced, the shock wave structure forms; otherwise, the soliton forms due to the balance between the dispersive term and the nonlinear term. We show that the effect of superthermal electrons is more influence in comparison with the superthermal ions on the behavior of the shock waves. It is also seen that increasing relative density ( ) decreases the amplitude of shock wave except for very small value of . Our investigation is of wide relevance to astronomers and space scientists working on interstellar space plasmas.